On the thermodynamic properties of the generalized Gaussian core model - Mladek, B.M.; Fernaud, M.J.; Kahl, G.; Neumann, M. (Condensed Matter Physics, 2005)
We present results of a systematic investigation of the properties of the
generalized Gaussian core model of index n. The potential of this system
interpolates via the index n between the potential of the Gaussian core
model and the penetrable sphere system, thereby varying the steepness
of the repulsion. We have used both conventional and self-consistent liquid
state theories to calculate the structural and thermodynamic properties of
the system; reference data are provided by computer simulations. The results
indicate that the concept of self-consistency becomes indispensable
to guarantee excellent agreement with simulation data; in particular, structural
consistency (in our approach taken into account via the zero separation
theorem) is obviously a very important requirement. Simulation results
for the dimensionless equation of state, βP/%, indicate that for an indexvalue
of 4 a clustering transition, possibly into a structurally ordered phase
might set in as the system is compressed. Ми представляємо результати системного дослідження властивостей узагальненої моделі гаусового кора з індексом n. Потенціал такої системи з допомогою індексу n, що визначає крутизну притягання, дозволяє інтерполювати взаємодії від моделі гаусового кора до системи проникних сфер. Для розрахунку структурних і термодинамічних властивостей нами використовувалися як традиційні, так і самоузгоджені версії теорії рідкого стану, а система відліку бралася з комп’ютерного експерименту. Результати показують, що для отримання доброго узгодження з даними моделювання концепція самоузгодження стає обов’язковою; зокрема структурне узгодження, яке у нашому підході проводиться через теорему нульового розділення, є надзвичайно важливою вимогою. Результати моделювання для обезрозміреного рівняння стану, βP/%, вказують на те, що для моделі з індексом 4 може виникати структурно впорядкована фаза (перехід кластерування) при стисканні системи.